(untitled) (Ozone Therapy Global Journal, 2011)
For treatment of 100 patients with non-specific colpitis a method of streaming Ozonetherapy was used with assistance of the ozone generator MEDOZONS-BM and special attachment on the basis of vaginal speculum. The irrigation with an ozone-oxygen mixture with ozone concentr ation of 2000 mcg/L was carried out within 5 minutes after preliminary moistening of mucosa with sterile bi-distilled water. In the course of the investigations it was established that along with a positive clinical effect, ozonetherapy caused an impr ovement in vag i nal local immunit y ind i ces – a credible increase in lysozyme in 70% of patients, a decrease in IgG level in 60% of patients, stabilization of cervical mucus myeloperoxidase in 80% of patients. Also we have used intrauterine irrigations with ozonized bi-distilled water in case of acute endometritis. This method of treatment has been provided to 100 patients with postnatal and postabortive endometritis. Based on the received results, we have drawn a conclusion that in the course of treatment all patients showed an improvement in general state, body temperature returned to normal, symptoms of intoxication decreased, sleep and appetite got better, pain syndrome disappeared faster and pathological discharges were eliminated. The results of laboratory investigations have demonstrated a credible decrease in ESR, normalization of leukocyte numbers and an decrease in circulating immune complexes. Thus, for treatment of non-specific colpitis and endometritis we may recommend the given method of ozonetherapy to be used in combination with a basic anti-inflammatory therapy.